(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we introduce and investigate a class of bi-univalent functions, denoted by F(n, α, β), that depends on the Ruscheweyh operator. For functions in this class, we derive the estimations for the initial Taylor-Maclaurin coefficients |a_2| and |a_3|. Moreover, we obtain the classical Fekete-Szegö inequality of functions belonging to this class.